Digital Technologies for the Future of the Water Sector? Examining the Discourse on Digital Water - Walter, Christina (Geoforum, 2024)
•The water sector is being transformed through the implementation of digital technologies.•Analysing the discourse on digital water through Political Ecology and STS.•The discourse frames digital technologies as the solution to current and future water challenges.•Socio-technical imaginaries of the future are transported trough the discourse of digital water. Global climate change increases the uncertainty about water, its availability and quality. Thus, the water sector is being transformed to react to the rising water demand as well as climate change and water quality issues and is transitioning into its so-called „fourth revolution“: aiming towards a more sustainable and resilient management of water, whilst simultaneously encountering the mega-trend of digitalisation. Through adopting digital technologies, the sector has the opportunity to address the 21st-century water risks early on as the new technologies will increase the knowledge of water supply, water demand and other water data which can be used to inform public policy or new investments. In this paper, I critically examine the discourse on digital water and how it is expressed, through the lens of Political Ecology. This is enriched through insights of Science and Technology Studies (STS). The discourse on digital water is characterised by two distinct argumentative pathways: On the one hand, technological solutionism presents digital technologies as the only solution to the challenges within the water sector, and on the other hand, socio-technical imaginaries of the future which constitute digital water as a new pathway within the water sector. This portrays a positive and optimistic future for the development of the water sector which is achieved through the implementation of digital technologies.